دراسة تحليلية لواقع إجراءات تصدير المنتجات الزراعية - دعاء, قروي; فتيحة, بقاص; نجاح, قدوري (جامعة الوادي - University of Eloued, 2023)
"تبحث الدراسة في تحليل إجراءات المنتجات الزراعية لمؤسسات التصدير بولاية الوادي، حيث قمنا في هذي الدراسة بتتبع الإطار النظري والدراسة الأدبية لكل من المنتجات الزراعية والتصدير، وقد إستعملت هذه الدراسة المنهج الوصفي والتحليلي وإستعمال طريقة المقابلة مع المؤسسات، إعتمادا على المعطيات والإحصائيات الواردة من الغرفة التجارية، والمؤسسات قيد الدراسة. ومن خلال ذلك توصلنا إلى أن عملية تصدير المنتجات الزراعية تمر بعدة إجراءات منها إجراءات من أجل الشركة,الإجراءات المسبقة للنجاح في عملية التصدير والتكوين والتحضير لعملية التصدير، حيث نجد أن تصدير المنتجات الزراعية أصبح محل إهتمام للمؤسسات المتواجدة بالولاية, ولعملية التصدير عدة إجراءات محفزة ترتكز على منح معاملة تفضيلية لمؤسسات التصدير ومساعدة والدعم في تصدير ومحفزات الضريبية عند التصدير، وهذا ما أدى إلى تشجيعهم وتنويع المنتجات المصدرة والحرص على جودتها للوصل بها إلى الأسواق الدولية, ومن جهة أخرى هناك عراقيل تعيق هذه المجهودات المبذولة من طرف المؤسسات وهو الحاجز الذي يبقي المنتجات الزراعية داخل الوطن مع وجود الفائض الكبير وبأعلى جودته." " ABSTRACT: This study examines the analysis of procedures related to agricultural products implemented by exportation firms in the Wilaya of El-Oued. The study commences by synthesizing the theoretical framework and the literature review related to both agricultural products and exportation. The descriptive and analytical methods are used together with the interview of some firms based on the data and statistics received from the Chamber of Commerce and the firms under study. Through this study, we concluded that the process of exporting agricultural products goes through several procedures, including procedures established by companies, anticipated procedures for a successful export process, in addition to the training and preparation of the export process. In this respect, we concluded that exporting agricultural products has become a matter of interest for the companies located in the wilaya, especially that the export process benefits from several stimulating procedures, including the grant of preferential advantages to export companies, assistance and support in exporting, and tax incentives upon export. These benefits have led to the encouragement and diversification of exported products and ameliorated the quality of products to meet the standards of international markets. On the other hand, there are obstacles that impede the export efforts made by companies, which represent a barrier that prevent the export of a large surplus of agricultural products despite their high quality."
Keywords: منتجات الزراعية، تصدير، تسويق المنتجات الزراعية.; Agricultural products, export, marketing of agricultural products